Mechanical Stability of the Prodisc-C Vivo Cervical Disc Arthroplasty: A Preliminary, Observational Study Using Radiostereometric Analysis. Issue 3 (May 2020) - van Hooff, Miranda L.; Heesterbeek, Petra J. C.; Spruit, Maarten
Study Design: Prospective cohort study. Objective: To investigate the primary stability of the Prodisc-C Vivo cervical disc arthroplasty with regard to the adjacent cervical vertebrae using radiostereometric analysis (RSA), and to monitor its clinical performance. Methods: Sixteen patients with degenerative cervical disc disease were included. RSA radiographs were obtained at the first postoperative day, at 6 weeks, 3 months, and 6 months postoperatively. Migration (translation [mm]) of the superior and inferior implant components were measured with model-based RSA, expressed along the 3 orthogonal axes, and calculated as total translation. Clinical outcomes were Neck Disability Index, numeric rating scales for neck and arm pain, Likert-type scales for satisfaction, and adverse events. Range of motion was reported as C2-C7 flexion-extension mobility (ROM). Results: At final follow-up, no significant increase over time in median total translation was found. One inferior and 3 superior components subsided but were asymptomatic. ROM remained stable and clinical outcomes improved over time. Although 3 patients were unsatisfied and 3 adverse events occurred, this was not related to translation of the components. Conclusions: On a group level, both components of the Prodisc-C Vivo cervical disc arthroplasty remained stable over time and below the clinical threshold of 1 mm. Individual outliers for translation were not clinically relevant and probably related to settling of the components into the vertebral endplates. RSA allowed us to perform a preliminary but accurate study on the micromotion of a new cervical disc replacement in a small sample size, without putting large numbers of patients at risk.